Neuroimmunological communication via CGRP promotes the development of a regulatory phenotype in TLR4‐stimulated macrophages. Issue 12 (10th November 2014) - Baliu‐Piqué, Mariona; Jusek, Gabriela; Holzmann, Bernhard
Abstract : Environmental signals shape the phenotype and function of activated macrophages. Here, we show that the neuropeptide calcitonin gene‐related peptide (CGRP), which is released from sensory nerves, modulates the phenotype of TLR4‐activated murine macrophages by enhancing expression of the regulatory macrophage markers IL‐10, sphingosine kinase 1 (SPHK1), and LIGHT (lymphotoxin‐like, exhibits inducible expression and competes with HSV glycoprotein D for herpesvirus entry mediator, a receptor expressed by T lymphocytes). In contrast, CGRP inhibits production of cytokines characteristic of inflammatory macrophages and does not affect expression of wound‐healing macrophage markers upon TLR4 engagement. In IL‐4‐stimulated macrophages, CGRP increased LIGHT expression, but failed to induce IL‐10 and SPHK1. The stimulatory effect of CGRP on IL‐10 production required activation of protein kinase A and was linked to prolonged phosphorylation of CREB and sustained nuclear accumulation of CRTC2 and CRTC3 (where CRTC is CREB‐regulated transcriptional cofactor). CGRP enhanced expression of regulatory macrophage markers during the early, but not late, phase of LPS‐stimulation and this effect was independent of autocrine type‐I IFN activity. In contrast, autocrine type‐I IFN activity and treatment of macrophages with IFN‐β promoted late‐phase IL‐10 production, but had only minor influence on LIGHT and SPHK1 expression. Together, the results identify neuroimmunological communication through CGRP as a novel costimulatory pathway promoting the development of a regulatory phenotype of TLR4‐stimulated macrophages. CGRP appears to act through a mechanism that involves sustained activation of CREB‐dependent gene transcription.